Buprenorphine/Naloxone Maintenance Therapy: an Observational Retrospective Report on the Effect of Dose on 18 months Retention in an Office-Based Treatment Program - Theodore V Parran; AG Mace; Yael J Dahan; Christopher A Adelman; Mykola Kolganov (SAGE Publishing, 2017)
Context and objective: Buprenorphine has been available with few reports of the dose range necessary to adequately maintain patients. We report on the effect of 8 mg/d versus 16 mg/d of buprenorphine on long-term patient retention in office-based opioid maintenance (OBOMT). Design, setting, and participants: Case series, at an urban hospital-based primary care clinic providing OBOMT to 157 opiate-dependent, low socioeconomic status, uninsured, nonhomeless patients. Intervention: The OBOMT program operated by a comprehensive sobriety treatment program experienced State funding cuts. Thus, after 2 years, the program was required by the State funder to decrease the buprenorphine maintenance dose from 16 to 8 mg/d for all new admissions. We report on patient retention before and after dose reduction. Main outcome measures: The primary outcomes of this study were to measure and compare patient retention in the 2 cohorts at each point of treatment transition over the 18 months following OBOMT initiation. Results: No significant differences in patient retention were observed between the 16 and 8 mg/d patient cohorts. Lower dose buprenorphine maintenance (8 mg/d) in uninsured patients enrolled in publicly funded long-term OBOMT combined with comprehensive sobriety counseling was as effective as higher dose therapy (16 mg/d) in promoting patient retention throughout the study period. This lower dose resulted in a substantial saving to the public funding agency. Conclusions: In an observational retrospective report, retention in treatment of opiate-addicted patients was the same at 8 and 16 mg/d buprenorphine doses after 18 months. These data have implications for public and managed care funding of OBOMT, for the general prescribing of buprenorphine in outpatient care, and may be instructive in the ongoing debate about the relationship between buprenorphine dose.